Audio intelligent monitoring at the edge (AIME) for polyphonic sound sources - Lim, Victor (Nanyang Technological University, 2024)
Urban sound monitoring remains imperative as an effort to control and mitigate noise pollution, especially in urban areas. With the advancement in the field of artificial intelligence (AI) and edge computing, the development of intelligent machine listening systems for real-time noise monitoring has been a prominent focus in modern sound monitoring systems.